THE EFFECT OF THE ACHIEVEMENTS OF THE FINANCIAL STATEMENTS OPINION, INTERNAL CONTROL SYSTEM, AND EVALUATION SCORE OF PERFORMANCE ACCOUNTABILITY TO THE STATE LOSSES AT THE PUBLIC SECTOR INSTANCES IN INDONESIA - Khair, Almanna; Rahman, Aulia Fuad (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
The objective of this research was to analyze the effect of the achievements of the financial statements opinion, internal control system, and evaluation score of performance accountability to the state losses. Secondary data of those variables were collected from 54 ministries and institutions of the government for the period of 2010 to 2013. This research is quantitative descriptive with multiple regression analysis method. The results of the research showed that simultaneously achievements of the financial statements opinion, internal control system, and evaluation score of performance accountability had positive and significant effect on the state losses. Partially, achievements of the financial statements opinion and internal control system had positive and significant effect on the state losses while evaluation score of performance accountability had negative and not significant effect on the state losses.Keywords : Financial Statements Opinion, Internal Control System, Evaluation Score of Performance Accountability, State Losses